Avoidable mortality among parents whose children were placed in care in Sweden: A retrospective matched cohort study - Wall-Wieler, Elizabeth; Vinnerljung, Bo; Liu, Can; Roos, Leslie; Hjern, Anders (International Journal of Population Data Science, 2018)
Introduction Separation from one’s child can have significant consequences for parental health and well-being. Objectives and Approach We aimed to investigate whether parents whose children were placed in care had higher rates of avoidable (amenable and preventable) mortality. Data were obtained from the Swedish national registers. Mortality rates among parents whose children were placed in care between 1990 and 2012 (17 505 mothers, 18 286 fathers) were compared with a 5:1 matched cohort of parents whose children were not placed. We computed rate differences and hazard ratios of all-cause and avoidable mortality. Results When compared with parents who did not have a child placed in care, there were an additional 21 avoidable deaths per 10 000-person years among mothers and an additional 27 avoidable deaths per 10 000-person years among fathers whose children were placed in care. Among mothers, death due to preventable causes were 3·83 times greater (95% CI 2·82-5·21) and deaths due to amenable causes were 3·12 times greater (95% CI 2·07-4·69) for those whose children were placed in care. Among fathers, death due to preventable causes was 1·75 times greater (95% CI 1·41-2·16) and deaths due to amenable causes were 1·52 times greater (95% CI 1·08- 2·13) for those whose children were placed in care. Avoidable mortality rates were higher among mothers whose children were young when placed in care and parents whose children were all placed in care. Conclusion/Implications Mothers who had a young child placed and parents whose children were all placed in care are at much higher risk of avoidable mortality than parents whose children were not placed in care. Targeted public health interventions and more attentive health care could reduce risk of avoidable mortality in this group of parents.